Perkembangan Industri Content Aggregator dalam Pemberitaan Online: Studi Kasus pada Konten Berita di Line Today - Sahrul Haetamy Ananto (Mahesa Research Center, 2021)
The development of internet technology itself has had an influence on the existence of media, including the emergence of online media. Because online media allows for faster dissemination of information but sacrifices the basic principles of journalism, one of which is the accuracy of news. The Line Today feature as a product of internet development is an online news portal that positions itself as a content aggregator, namely a method of compiling news by publishing a number of news from other media. Therefore, the purpose of this study is to find out about the content aggregator in online news on the online news portal Line Today. This research is a qualitative descriptive study, data collection techniques using observation. By using the approach of medium theory, new media, and content aggregator, the results of this study indicate that the shift of conventional mass media to digital is part of the development of new media. It is also known that in online media, there is an important role for content aggregators as part of online news portals. In addition, as an online news portal that positions itself as a content aggregator, Line Today collects and selects news from online media that have collaborated to be republished.